A critical review on silver nanoparticles: From synthesis and applications to its mitigation through low-cost adsorption by biochar. (1st March 2021) - Islam, Md Anwarul; Jacob, Mohan V.; Antunes, Elsa
Abstract: Silver nanoparticles are one of the most beneficial forms of heavy metals in nanotechnology applications. Due to its exceptional antimicrobial properties, low electrical and thermal resistance, and surface plasmon resonance, silver nanoparticles are used in a wide variety of products, including consumer goods, healthcare, catalysts, electronics, and analytical equipment. As the production and applications of silver nanoparticles containing products increase daily, the environmental pollution due to silver nanoparticles release is increasing and affecting especially the aqueous ecosystem. Silver nanoparticles can kill useful bacteria in soil and water, and bioaccumulate in living organisms even at low concentrations from 10 −2 to 10 μg/mL silver can show antibacterial effect. On the other hand, the maximum silver discharge limit into freshwater is 0.1 μg/L and 3.2 μg/L for Australia and the USA, respectively. To reduce its toxic consequences and meet the regulatory guidelines, it is crucial to remove silver nanoparticles from wastewater before it is discharged into other water streams. Several technologies are available to remove silver nanoparticles, but the adsorption process using low-cost adsorbents is a promising alternative to mitigate silver nanoparticle pollution in the bulk stage. As one of the low-cost adsorbents, biochar produced from the biomass waste could be a suitable adsorbent. This review focuses on collating the latest evidence on silver nanoparticle production, applications, environmental consequences, and cost-effective technological approaches for silver removal from wastewater. Highlights: Silver nanoparticles and ions are toxic to living organisms. Adsorption is a sustainable process for silver removal from wastewater. Silver adsorption by low-cost biochar is efficient in a wide range of conditions. Modification of biochar properties enhance adsorption rate and reusability. Biochar-graphene composites demonstrate high silver adsorption.